Exercise intervention attenuates hyperhomocysteinemia-induced aortic endothelial oxidative injury by regulating SIRT1 through mitigating NADPH oxidase/LOX-1 signaling - Chan, Shih-Hung (Redox Biol, 2017)
Coronary artery disease (CAD) is a critical cardiovascular disease and a cause of high morbidity and mortality in this world. Hyperhomocysteinemia (HHcy) has been suggested as a risk factor for CAD. In addition, SIRT1 (sirtuin 1) has been reported to play a protective role in a variety of diseases, especially in the cardiovascular system. The main purpose of this study was to investigate the effects of exercise training on apoptosis and inflammation in HHcy animals. We also tested whether exercise protected against Hhcy-induced dysfunction of endothelium through modulation of SIRT1. C57BL mice (8 in each group) were fed with or without 1% L-methionine (w/w) in water for 4 months to induce HHcy. We found that Hhcy repressed SIRT1 and AMPK expression and increased NADPH oxidase activity. Plasma MDA, endothelium LOX-1 and p-p38 were up-regulated by Hhcy induction. NF-κB and it downstream molecules were activated under Hhcy situation, thereby promoting pro-inflammatory responses. Moreover, we also reported that Hhcy caused endothelium apoptosis involving Akt inhibition and mitochondria-dependent apoptotic pathways. Exercise training significantly protected against endothelium from Hhcy caused oxidative injuries. In addition, EX527 (SIRT1 inhibitor) reduced the therapeutic effects by exercise. Our results had indicated that exercise training prevent the development of atherosclerosis through SIRT1 activation and oxidative stress inhibition under Hhcy situation.